Assessment of the primary healthcare structure in the Kurdistan Region of Iraq: a narrative review - Shabila, Nazar P. (Family Medicine & Primary Care Review, 2026)
The structure of the primary care system provides important conditions for the process of care and its outcomes. The structure of primary care includes three dimensions: governance, economic conditions, and workforce development. There is a dreadful need to reorganize and restructure the primary care system in the Kurdistan Region of Iraq as part of the whole health system. However, limited publications discuss the challenges and needs of the primary care system in an organized and comprehensive manner. Therefore, this study reviewed the relevant literature to evaluate the structure dimension of the primary care system in the Kurdistan Region of Iraq and to determine its challenges, needs, opportunities, and potential barriers to improvement. The primary healthcare system in the Kurdistan Region of Iraq faces significant challenges, including poor governance, inadequate funding, and workforce misallocation. Weak planning, ineffective monitoring, underdeveloped infrastructure, and conflicts of interest between the public and private sectors hinder its efficiency. Limited financial investment and centralized decision-making further delay urgent health interventions. Additionally, the increasing number of specialists working in primary care centers undermines the core principles of family medicine. Key priorities to improve the system include strengthening governance through better leadership and service organization, adopting family medicine practices, ensuring proper financial decentralization, and enhancing workforce development by prioritizing the training and recruitment of qualified family physicians.